The relationship between system star rating and civil servant motivational and commitment level / Marvin Nasib Daranpin and Nabila Ismail - Daranpin, Marvin Nasib; Ismail, Nabila (2015)
This study was conducted to investigate the motivation and commitment level of employees towards their job after the System Star Rating and to investigate the relationship between the stars awarded and motivation and commitment level in two different public agencies. In total, 60 usable questionnaires were obtained in two public organization located at Kota Kinabalu, Sabah which are the Suruhanjaya Perkhidamatan Awam Negeri Sabah and Kementerian Perindustrian Infrastruktur. Both of these organizations have different stars rewarded. The result indicated that the relationship between stars awarded is significantly correlated with motivation and commitment of employees towards their job. This study also discussed the implication of this findings, limitations and recommendations for organization further study.